High-resolution sensitivity studies with the regional climate model COSMO-CLM - Meißner, Cathérine (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung der Universität Karlsruhe (TH), 2008)
High-resolution regional ensemble climate simulations with the regional climate model COSMO-CLM are performed for Southwest Germany to study the sensitivity of meteorological and hydrological variables to parameter settings. The soil-vegetation model VEG3D is implemented into COSMO-CLM to assess the impact of the lower atmospheric boundary on simulation results. A statistical-dynamical downscaling method is tested to shorten the simulation time for regional climate studies.